Solution blowing of thermoplastic polyurethane nanofibers: A facile method to produce flexible porous materials - ŞİMŞEK, RAMAZAN; POLAT, YUSUF (WILEY-BLACKWELL, 2016)
Solution blowing (SB) is a promising and scalable approach for the production of nanofibers. Air pressure, solution flowrate, and nozzle-collector distance were determined as effective process parameters, while solution concentration was also reported as a material parameter. Here we performed a parametric study on thermoplastic polyurethane/dimethyl formamide (TPU/DMF) solutions to examine the effect of such parameters on the resultant properties such as fiber diameter, diameter distribution, porosity, and air permeability of the nanofibrous webs. The obtained solution blown thermoplastic polyurethane (TPU) nanofibers had average diameter down to 170 +/- 112 nm, which is similar to that observed in electrospinning. However, the production rate per nozzle can be 20 times larger, which is primarily dependent on air pressure and solution flow rate (20 mL/h). Moreover, it was even possible to produce nanofibers polymer concentrations of 20%; however, this increased the average nanofiber diameter. The fibers produced from the TPU/DMF solutions at concentrations of 20% and 10% had average diameters of 671 +/- 136 nm and 170 +/- 112 nm, respectively. SB can potentially be used for the industrial-scale production of products such as nanofibrous filters, protective textiles, scaffolds, wound dressings, and battery components. (C) 2015 Wiley Periodicals, Inc.
Keywords: electrospinning; fibers; membranes; polyurethanes; textiles; ELECTROSPINNING PROCESS; FIBERS; ELASTOMERS